Effects of Temperature and Water on Mechanical Properties, Energy Dissipation, and Microstructure of Argillaceous Sandstone under Static and Dynamic Loads. (20th July 2020) - Zhang, Rongrong; Ma, Dongdong; Su, Qingqing; Huang, Kun
Abstract : RMT-150B rock mechanics and split Hopkinson pressure bar (SHPB) devices were adopted to investigate the physical and mechanical properties, energy dissipation, and failure modes of argillaceous sandstone after different high temperatures under air-dried and saturation states. In addition, SEM and EDS tests were conducted to investigate its microstructure characteristics. Results showed that both the P-wave velocity and density of argillaceous sandstone specimen decreased with the increase of high temperature, while its porosity increased. Compared with static stress-strain curves, there was no obvious compaction stage for dynamic stress-strain curves, and the decrease rate of dynamic curves after peak strain was obviously slow compared with static curves. Both the static and dynamic strengths of argillaceous sandstone specimens decreased with increasing temperature, and the critical temperature point for the strength of argillaceous sandstone was 400°C. At the same temperature, the specific energy absorption under air-dried state was generally smaller compared with that under saturated state. Both the strain rate and temperature showed significant effect on the failure mode. After 100∼1000°C heat treatment, the granular crystals of the clastic structure gradually became larger, and both the number and average size of the original pores decreased, resulting in the deterioration of mechanical properties of argillaceous sandstone specimen.